(untitled) (Research, Society and Development, 2020)
This article aims to add to the investigations about the textbook and investigate the functions and effectiveness that visual communication exercises in the publication adopted by the Philosophy discipline of the Federal Institute of Education, Science and Technology of Ceará - Campus de Fortaleza - in technical courses integrated to high school. Based on this effort, which will use visual analysis tools such as Semiotics and Gestalt, we intend to evaluate how photos, illustrations, cartoons, works of art, comics, among other visual elements, promote the liberating philosophical reflection that allows the student break with the strictly technical education to which the working classes have historically been subjected and guide them towards the category of training advocated by the authors dealing with professional and technological education, that is, integral or omnilateral training. Thus, it is possible to offer contributions that make it possible to evaluate the ways in which the image has been used in the context of teaching-learning practice so that it can extract the maximum of the imagery resources and reinforce among teachers, pedagogical coordinators, editors, graphic designers, illustrators, artists and all those involved in the production and use of didactic material on the importance of a critical and vast visual repertoire in the process of unveiling the world beyond what words can describe.